2022
DOI: 10.3390/ijms231911842
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Transcriptomic Responses of Growth in Neolamarckia cadamba Stimulated by Exogenous Gibberellins

Abstract: (1) The phytohormones gibberellins (GAs) play a crucial role in plant growth and development, such as seed germination, flowering, fruiting, and stem elongation. Although many biological roles of GAs have been studied intensively, the molecular mechanisms of GAs in woody plants are still unclear. (2) In this study, we investigated the effects of exogenous application of GAs on Neolamarckia cadamba. (3) The height and biomass of N. cadamba increased after 7 days of GA treatment, especially on the second interno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 80 publications
1
8
0
Order By: Relevance
“…GA 3 plays crucial roles in the processes of growth, seed germination, physicochemical properties, nutrient uptake, secondary metabolism, and stress response in plants [30,31]. The previous results showed that exogenous GA 3 promoted the growth of Neolamarckia cadamba and Camellia sinensis seedlings and increased the biomass [7,32]. At the same time, GA 3 enhanced the chlorophyll content but reduced carotenoid content in the leaves of Valencia oranges, suggesting that GA 3 promoted growth by improving chlorophyll content in plants [33].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…GA 3 plays crucial roles in the processes of growth, seed germination, physicochemical properties, nutrient uptake, secondary metabolism, and stress response in plants [30,31]. The previous results showed that exogenous GA 3 promoted the growth of Neolamarckia cadamba and Camellia sinensis seedlings and increased the biomass [7,32]. At the same time, GA 3 enhanced the chlorophyll content but reduced carotenoid content in the leaves of Valencia oranges, suggesting that GA 3 promoted growth by improving chlorophyll content in plants [33].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated that exogenous GA 3 significantly improves the photosynthetic pigment content, photosynthetic efficiency, soluble substance content, and antioxidase activities. Concurrently, it increases the fresh weight and plant height, subsequently promoting plant growth [2,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GAs is a common plant hormone first identified from fungus Gibberella fujikuroi , which was investigated to promote the stem elongation in many plants ( Eriksson et al., 2000 ; Claeys et al., 2014 ). The cell length in the second internode of Neolamarckia cadamba was also significantly increased after exogenous application of GAs ( Li et al., 2022 ). The GA-deficient mutant with dwarf phenotype further proved the roles of GAs in regulating the plant height ( Ashikari et al., 1999 ; Sakamoto et al., 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…bHLH74 is required for leaf and root development in Arabidopsis [59]. In Neolamarckia cadamba, bHLH74 has been reported to function in cell elongation and is upregulated after gibberellin treatment [60]. In tomatoes, SlbHLH96 interacts with SlERF4 and represses the expression of ABA catabolic genes, thereby promoting drought tolerance [61].…”
Section: Discussionmentioning
confidence: 99%